Intravital Multiphoton Imaging of the Bone and Bone Marrow Environment. Issue 5 (23rd November 2019) - Kim, JungMo; Bixel, Maria Gabriele
Abstract: Over the last two decades, numerous advances in our understanding of bone cell biology and bone mineral homeostasis have been achieved. As a dynamic connective and supportive tissue, bone is constantly sensing and responding to both external mechanical forces and internal systemic and local signals. A variety of intravital imaging approaches have been investigated to identify molecular and cellular processes and to decipher signaling pathways involved in the cellular communication between different types of bone cells that form bone multicellular units. Furthermore, bone multicellular units interact with cells of the immune and hematopoietic system to maintain bone homeostasis. Bone‐forming osteoblasts and bone‐degrading osteoclasts are situated on the endosteal surface of bone influencing the dynamic remodeling and the regeneration of bone tissue. Osteocytes are found at very unique locations in the bone, closely surrounded by bone matrix, forming a cellular network through their interconnected dendritic processes. Bone marrow cells fill the numerous large cavities inside the bones with various blood cell lineages arising from hematopoietic stem and progenitor cells. A highly complex and interconnected network of arterial vessels and sinusoidal capillaries span through the bone marrow spaces forming an interface between the blood circulation and the bone marrow which allows cell trafficking between both compartments. Live imaging of animals using multiphoton microscopy represents a powerful approach to address the cellular behaviors of bone and bone marrow cells over time and space in their natural tissue microenvironment. The in vivo environment is crucial, because the dynamic behavior of cells is critically influenced by many tissue factors including extracellular components, cytokine and growth factor gradients, and fluid forces, such as blood flow. The review article focuses upon recent advances in multiphoton imaging technologies as well as novel experimental approaches in the understanding of the dynamic molecular and cellular mechanisms underlying bone tissue homeostasis, remodeling, and regeneration under physiological and pathological conditions. © 2019 The Authors. Cytometry Part A published by Wiley Periodicals, Inc. on behalf of International Society for Advancement of Cytometry.